2014
DOI: 10.1016/j.sbspro.2014.12.439
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Macedonian High School Students towards the Environment

Abstract: The objective of this study was to examine the attitudes of Macedonian high school students towards the environment. Attitudes reflect feelings of concern for the environment. They are mental states based on personal beliefs towards pollution, technology, interdependence and equal importance of all life forms, dependence of human life on the resources of a finite planet, power of human beings to modify the environment, conservation, environmental action etc. The survey was carried out in 18 cities and towns. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…Sci. 2018, 7, x FOR PEER REVIEW 3 of 16 Makki et al 2003;Dillon and Gayford 1997;Ozkan 2013;Asan et al 2014). Higher pro-environmental attitudes were found among biology/science students than among non-science students (Hassan et al 2010;Tikka et al 2000).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. 2018, 7, x FOR PEER REVIEW 3 of 16 Makki et al 2003;Dillon and Gayford 1997;Ozkan 2013;Asan et al 2014). Higher pro-environmental attitudes were found among biology/science students than among non-science students (Hassan et al 2010;Tikka et al 2000).…”
Section: Study Areamentioning
confidence: 99%
“…There are several studies that have investigated students' attitude and behavior towards environmental protection and EE (Uitto and Saloranta 2010;Ugulu et al 2013;Hassan et al 2010;Makki et al 2003;Dillon and Gayford 1997;Ozkan 2013;Asan et al 2014). Higher pro-environmental attitudes were found among biology/science students than among non-science students (Hassan et al 2010;Tikka et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For Aziz et al (2012), basic knowledge about sustainable development has a strong correlation to the development and improvement of students' attitude towards sustainability. Asan et al (2014) concluded that high school students tend to show more concern about environmental problems. On the other hand, De Leeuw et al (2014) revealed that different behaviours towards sustainability condition the students' intention to participate in environmentally sustainable behaviours, compared to their intention to conduct socially sustainable behaviours.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This process produces effects on the environment, culture, political systems, development and economic prosperity, as well as on the well-being of people who make up societies around the world (Baylis et al 2017). It has led some authors (Aziz et al 2012;Asan et al 2014;De Leeuw et al 2014;Tucker and Izadpanahi 2017;Al-Naqbi and Alshannag 2018) to ponder over the importance of measuring variables such as the behaviour, attitude and knowledge of students toward sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental worldview in the Republic of Macedonia have been studied by many authors: Srbinovski 2001Srbinovski , 2004Srbinovski , 2005aSrbinovski , 2005bSrbinovski , 2006Ismaili et al, 2009;Idrizi et al, 2014 etc. In the last twenty years approximately 74% of Macedonian students have been demonstrated mainly pro-environmental attitudes.…”
Section: Gender Differences In Environmentalism: a Case Study Of Macementioning
confidence: 99%